Artificial intelligence: Essential to Successful Consumer Acquisition for the Consumer Electronics Goods Industry in Bangladesh. A study on Walton Hi Tech Industries Ltd. - Islam, MD. Wasib (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.